Rainfall and Hydrograph Styles in Ephemeral Streams of the Drylands of Patagonia (South America–Argentina) - Gabriel Kaless; Héctor Malnero; Oscar Frumento; Miguel Pascual (Water Resources Research)
Abstract Ephemeral streams in dry environments can convey high intensity sediment‐laden flash floods. The study of these events is quite difficult due to remote locations with limited accessibility, unexpected events, rough weather conditions and safety concerns. Hence combined data of rainfall and flood hydrograph is rather scarce in the world, and null in Patagonia‐South America. The Experimental Basin Arroyo Sagmata (total drained area of 129 km2), located in the Lower Valley of the Chubut River has been equipped with 4 rain gauges, and 4 time‐lapse cameras in four reaches of the arroyos. Data from a 4‐year monitoring provides valuable insights about the hydrological response of basins in the drylands of Patagonia, such as the time of response, the shape of hydrographs and its relation with the hyetographs. Four hydrograph styles have been observed: single‐peak (S), multi‐peaks (M), flat‐top (F) and compound (C) peaks. Rainfall styles have also been classified into single, multiple and compound. Soil processes operate reducing the number of peaks (M‐type hyetographs are transformed into S‐ or M‐type hydrographs). The rain structure is also important, especially when the high intensity occurs in the beginning of the event. Channel connectivity pattern and disconnections explain the observation of M‐type hydrograph and F‐type hydrograph, respectively.